Analysis of the Effectiveness of Implementing Project-Based Learning Models on Students' Critical Thinking Skills in Elementary Schools: A Systematic Literature Review - Dinda Antika Putri; Sumarno; Berta Apriza; Asri widianingrum (Journal for Lesson and Learning Studies, 2025)
The low level of critical thinking skills among elementary school students has become a major challenge in meeting the demands of 21st-century competencies. This issue is exacerbated by the lack of learning models that actively engage students in solving real-world problems and making decisions based on analytical reasoning. This study aims to analyze the effectiveness of implementing the Project-Based Learning (PjBL) model in enhancing students’ critical thinking skills at the elementary level. A Systematic Literature Review (SLR) was conducted by collecting data from Google Scholar using specific keywords. The search yielded 12,900 documents, which were narrowed down to 249 articles, with 10 articles ultimately meeting the inclusion criteria for further analysis. The data were analyzed descriptively and qualitatively to identify the main findings related to the application of PjBL in improving critical thinking. The results indicate that PjBL is effective in developing students’ abilities to analyze, evaluate, and solve problems logically and creatively. Additionally, this model enhances students’ social skills, collaboration, and communication. The findings suggest that PjBL should be more widely implemented in elementary education as an innovative learning strategy capable of fostering 21st-century skills in a sustainable manner.